Molecular identification of T-box transcription factor 6 and prognostic assessment in patients with congenital scoliosis: A single-center study - Zhang, Wenyan; Yao, Ziming; Guo, Ruolan; Li, Haichong; Zhao, Shuang; Li, Wei; Zhang, Xuejun; Hao, Chanjuan (Frontiers in Medicine, 2022)
Background Congenital scoliosis (CS) is characterized by vertebral malformations. The precise etiology of CS is not fully defined. A compound inheritance of TBX6 was identified in 10% of patients with CS in Han Chinese and formed a distinguishable subtype named TBX6-associated congenital scoliosis (TACS). Methods To investigate the variants and risk haplotype of TBX6, we recruited 121 patients with CS at Beijing Children’s Hospital. We collected the clinical characteristics and surgical treatment options and followed their postoperative prognoses. Results Eight patients (6.6%) were molecularly diagnosed with TACS and carried the previously defined pathogenic TBX6 compound heterozygous variants. All the eight patients with TACS had the typical TACS clinical feature of hemivertebrae in the lower part of the spine. These patients received posterior hemivertebra resection combined with segmental fusion. Follow-ups revealed satisfactory correction without postoperative complications. Conclusion We observed a 6.6% prevalence of TACS in our CS cohort. Follow-ups further highlighted that surgical treatment of hemivertebra resection combined with segmental fusion performed well with prognosis for patients with TACS. This could provide valuable information for CS individuals with compound heterozygosity in TBX6.